Exploring digital healthcare adoption among Malaysia senior citizen using DEMATEL: implications for closing the technology GAP / Noor Anis Munirah Mohd Hashim, Ku Nur Balqis Ku Ridzuan and Mohamad Nadjmi Nasiruddin - Mohd Hashim, Noor Anis Munirah; Ku Ridzuan, Ku Nur Balqis; Nasiruddin, Mohamad Nadjmi (2024)
This study's purpose was to identify and analyze the cause and effect of digital healthcare barriers among senior citizens. Based on a literature review, ten barriers were considered in the study and a questionnaire was used to interview twenty-four respondents that were categorized among senior citizens. According to the Department of Statistics Malaysia (DoSM), it has been recorded that 10.7% of Malaysia’s population consists of those aged 60 and above which are equivalent to some 3.5 million people for the year 2020. This study was conducted among senior citizens because according to research, it is shown that by 2040, people aged 65 and above will rise to 14.5% and the number is expected to grow. Because of Malaysia's ageing population, this could have an impact on the country's health. Two objectives have been achieved in this study. The first objective is to analyze the cause and effect that hinder senior citizens from using digital healthcare. The second objective is to recommend the good of digital healthcare adoption among senior citizens. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was used to evaluate the causal relationships among the proposed factors. By this method, the cause and effect of the barriers can be determined. The findings showed that based on the Ri+Ci value, B7 (Privacy and security concerns) placed first with a value of 30.9383 and B8 (Lack of personalized support) have the lowest value of 29.1731, indicating the least influence among all the barriers. To improve user comfort and confidence, it is recommended to address the concerns of technology among the elderly. This could involve training sessions, workshops, or user-friendly design elements in digital healthcare platforms.